ANALISA PENGARUH PEMBERIAN CAIRAN PENDINGIN (ETHYL ALCOHOL) PENGUCURAN LANGSUNG DAN PENGABUTAN (SPRAY) TERHADAP UMUR DAN KEAUSAN PAHAT HSS PADA PROSES MILLING VERTICALBAJA ST42 DENGAN VARIASI KECEPATAN POTONG - Soegiarto, Totok; Setyawan, Andy (Teknik Mesin S1 ITN Malang, 2008)
A tool life is an important data in planning a machining process. In this research, an experiment was done to study life and wear of HSS cutting tool used in milling process of an steel which has a strength tensile was 42 Kg/mm2. Conditions of research were used examination without cutting coolant method, sparayed cutting coolant method , and direct gushed method of cutting coolant. Cutting speed was varied with other cutting variables (federate and depth of cut) was set fixed. In this research used Ethyl Alcohol as cutting coolant. Graphical method was used in the analysis to determine exponential (n) and a constant of Taylor Tool Life (CT.).